Capitalismo y socialdemocracia / Adam Przeworski ; versión Española de Consuelo Vázquez de Parga - Vázquez de Parga, Consuelo; Przeworski, Adam (Alianza Universidad. Ciencias Sociales ; 571)
Bibliografía: p. 280-293